Long-term serological monitoring of Leishmania infantum in European wild rabbits (Oryctolagus cuniculus) in Mediterranean ecosystems of southern Spain - Jesús Barbero-Moyano; Moisés Gonzálvez; David Cano-Terriza; Saúl Jiménez-Ruiz; Sabrina Castro-Scholten; Débora Jiménez-Martín; Félix Gómez-Guillamón; Leonor Camacho-Sillero; Inmaculada Moreno; Mercedes Domínguez; Jonás Carmona-Pírez; Carlos Rouco; et al. (Preventive Veterinary Medicine, 2026)

Serum biomarkers of phthalate exposure, adipose tissue metabolites and 20-years incidence of elevated LDL levels: An exploratory exposome study in the GraMo cohort - Celia Pérez-Díaz; Axel Raux; Justine Massias; Bruno Le Bizec; Jean Philippe-Antignac; Yann Guitton; Inmaculada Salcedo-Bellido; Eduardo Linares Ruiz; Francisco M. Pérez-Carrascosa; Pilar Requena; Juan Pedro Arrebola; German Cano-Sancho (Environmental Toxicology and Pharmacology, 2026)

Impact of neoadjuvant cetuximab on liver function and tumor reduction in a murine model of selective portal vein ligation - Guillermo Tirado-Rodríguez; Inmaculada Ruiz-Montesinos; Sira Iturrizaga; Amador García Ruiz de Gordejuela; Paula Aizpiolea; Daniel Alonso-Alconada; Ignacio García-Alonso; Borja Herrero de la Parte (Clinical & Experimental Metastasis, 2025)
Colorectal cancer mortality is largely driven by metastatic spread, with colorectal liver metastases (CRLM) being the most frequent. Treatment often combines surgery and systemic therapy, including anti-EGFR agents such as cetuximab. This study evaluated the cytoreductive effect of cetuximab on CRLM and its influence on liver function and regeneration in a selective portal vein ligation (PVL) model. Sixty-six male WAG/RijHsd rats were used. Seven days before PVL, twelve tumor-bearing animals received intra-arterial cetuximab, while other six received vehicle (saline). Additional groups included tumor-bearing rats without PVL, rats undergoing PVL alone, and untreated controls (n = 6 each). Seven days after PVL, the future remnant liver volume (%FRL) and hepatocyte replication were quantified. Serum markers for hepatic, renal, and systemic injury were analyzed, and tumor volume was assessed by ultrasound before and after PVL. The regenerative response following PVL was not significantly affected by cetuximab, with %FRL reaching 80–90%. However, hepatocyte nuclei exhibited a smaller mean area compared with non-treated animals (45.35 ± 9.09 vs. 43.54 ± 9.87 μm²; p < 0.001). Liver function remained preserved, although glucose levels decreased after PVL. Cetuximab significantly reduced tumor growth driven by hepatic regeneration (1.12 ± 0.45 vs. 0.53 ± 0.16 mL; p < 0.01). Neoadjuvant intra-arterial cetuximab does not impair liver regeneration after PVL while effectively limiting tumor proliferation linked to regenerative stimuli. These findings support its perioperative safety and potential use to prevent tumor recurrence in patients with CRLM undergoing staged hepatectomy.

Characterisation of lung cell infiltration during the early stage of infection by porcine reproductive and respiratory syndrome virus type 1 strains of different virulence - Karola Fristiková; José María Sánchez-Carvajal; Carmen Álvarez-Delgado; Fernanda Larenas-Muñoz; Macarena Rodríguez-Ruiz; Inés Ruedas-Torres; Inmaculada Barranco; Francisco Javier Salguero; Francisco José Pallarés; Enric Mateu; Librado Carrasco; Irene Magdalena Rodríguez-Gómez; et al. (Veterinary Microbiology, 2025)

Adipose tissue cadmium concentrations as potential determinants of serum PON1 status in an adult cohort from Southern Spain - Maria Cruz Gomez Pellin; Eduardo Linares-Ruiz; Javier Esteban; Inmaculada Salcedo-Bellido; Gonca Çakmak; María Eugenia Velasco García; Jose Barril; Suylen Galbán-Velázquez; Celia Pérez-Díaz; Francisco M. Pérez-Carrascosa; Petra Vrhovnik; Željka Fiket; et al. (Environmental Toxicology and Pharmacology, 2025)

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Alterations in hepatic amino acid metabolism related to MASLD in individuals with obesity - Armando J. Pérez-Díaz; Inmaculada Ros-Madrid; María A. Martínez-Sánchez; Sara Rico-Chazarra; Alba Oliva-Bolarín; Andrés Balaguer-Román; Virginia E. Fernández-Ruiz; Carlos M. Martínez; José E. Yuste; Mercedes Ferrer-Gómez; Camilo J. Llamoza-Torres; María D. Frutos; et al. (Journal of Physiology and Biochemistry, 2025)

Raw milk at refrigeration temperature displays an independent microbiota dynamic regardless Listeria monocytogenes contamination - Alba Espí-Malillos; Inmaculada López-Almela; Pilar Ruiz-García; María Carmen López-Mendoza; Nerea Carrón; Pedro González-Torres; Juan J. Quereda (Food Research International, 2025)

Production of equol, dehydroequol, 5-hydroxy-equol and 5-hydroxy-dehydroequol in soy beverages by the action of dihydrodaidzein reductase in Limosilactobacillus fermentum strains - Susana Langa; José Antonio Curiel; Ana Ruiz de la Bastida; Ángela Peirotén; Inmaculada Álvarez; José María Landete (Food Chemistry, 2025)

HLA-C*07 is associated with symptomatic HIV-1-associated neurocognitive disorders (HAND) and immune dysregulation - Eduardo Pons-Fuster; Enrique Bernal; Concepción F. Guillamón; Lourdes Gimeno; María V. Martínez-Sánchez; Inmaculada Ruiz-Lorente; José A. Campillo; Diana Ceballos; Ana Torres; Cristina Tomás; Ángeles Muñoz; Antonia Alcaraz; et al. (Infectious Diseases, 2024)

Urinary neutrophil gelatinase-associated lipocalin as early biomarker for renal disease in dogs with leishmaniosis - Patricia Ruiz; Ángela Durán; María Gil; Inmaculada Sevidane; Jose Ignacio Cristóbal; Paloma Nicolás; Francisco Javier Duque; Concepción Zaragoza; Ana Belén García; Beatriz Macías-García; Rafael Barrera (Veterinary Parasitology, 2024)

Air Pollution PM10 Forecasting Maps in the Maritime Area of the Bay of Algeciras (Spain) - María Inmaculada Rodríguez-García; María Gema Carrasco-García; Maria da Conceição Rodrigues Ribeiro; Javier González-Enrique; Juan Jesús Ruiz-Aguilar; Ignacio J. Turias (Journal of Marine Science and Engineering, 2024)
Predicting the levels of a pollutant in a given area is an open problem, mainly because historical data are typically available at certain locations, where monitoring stations are located, but not at all locations in the area. This work presents an approach based on developing predictions at each of the points where an immission station is available; in this case, based on shallow Artificial Neural Networks, ANNs, and then using a simple geostatistical interpolation algorithm (Inverse Distance Weighted, IDW), a pollutant map is constructed over the entire study area, thus providing predictions at each point in the plane. The ANN models are designed to make 1 h ahead and 4 h ahead predictions, using an autoregressive scheme as inputs (in the case of 4 h ahead as a jumping strategy). The results are then compared using the Friedman and Bonferroni tests to select the best model at each location, and predictions are made with all the best models. In general, to the 1 h ahead prediction models, the optimal models typically have fewer neurons and require minimal historical data. For instance, the best model in Algeciras has an R of almost 0.89 and consists of 1 hidden neuron and 3 to 5 lags, similar to Colegio Los Barrios. In the case of 4h ahead prediction, Colegio Carteya station shows the best model, with an R of almost 0.89 and a MSE of less than 240, including 5 hidden neurons and different lags from the past. The results are sufficiently adequate, especially in the case of predictions 4 h into the future. The aim is to integrate the models into a tool for citizens and administrations to make decisions.

Dual functional materials based on Ni and different alkaline metals on alumina for the cyclic stepwise CO2 capture and methanation - Enrique García-Bordejé; Ana Belén Dongil; José M. Conesa; Antonio Guerrero-Ruiz; Inmaculada Rodríguez-Ramos (Chemical Engineering Journal, 2023)

Dietary intake of polychlorinated dibenzo-p-dioxins and furans, adiposity and obesity status. - Nadine Khoury; María Ángeles Martínez; Indira Paz-Graniel; Miguel Ángel Martínez-González; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (Environmental Research, 2023)

Multicompound biorefinery based on combined acid/alkaline-oxidative treatment of olive stones - Carmen Padilla-Rascón; Juan Miguel Romero-García; Inmaculada Romero; Encarnación Ruiz; Eulogio Castro (Process Safety and Environmental Protection, 2023)

Global longitudinal strain assessment of cardiac function and extravascular lung water formation after diving using semi-closed circuit rebreather - María Martinez-Villar; Antonio Tello-Montoliu; Agustín Olea; Ángel Pujante; Daniel Saura; Silvia Martín; Nereo Venero; Ana Carneiro-Mosquera; Nuria Ruiz de Pascual; Noelia Valero; Miguel Martinez-Herrera; Inmaculada Ramírez-Macías; et al. (European Journal of Applied Physiology, 2022)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Health-Related Lifestyles and Cancer-Preventive Behaviors of Medical and Nursing Students and Family Medicine Residents in Relation to the European Code Against Cancer - Esperanza Romero-Rodríguez; Luis Angel Pérula-de Torres; José Ignacio Moscosio-Cuevas; Roger Ruiz-Moral; Celia Jiménez-García; Inmaculada Olaya-Caro; Francisco Camarelles-Guillem (Journal of Cancer Education, 2021)

Recent clinical relevance of mono-genital colonization/infection by Ureaplasma parvum - Víctor Siles-Guerrero; Inmaculada Cardona-Benavides; Carmen Liébana-Martos; Fernando Vázquez-Alonso; Manuela Expósito-Ruiz; José María Navarro-Marí; José Gutiérrez-Fernández (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Use of a K-nearest neighbors model to predict the development of type 2 diabetes within 2 years in an obese, hypertensive population - Rafael Garcia-Carretero; Luis Vigil-Medina; Inmaculada Mora-Jimenez; Cristina Soguero-Ruiz; Oscar Barquero-Perez; Javier Ramos-Lopez (Medical & Biological Engineering & Computing, 2020)

Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Joaquín Tintoré; Nadia Pinardi; Enrique Álvarez-Fanjul; Eva Aguiar; Diego Álvarez-Berastegui; Marco Bajo; Rosa Balbin; Roberto Bozzano; Bruno Buongiorno Nardelli; Vanessa Cardin; Benjamin Casas; Miguel Charcos-Llorens; et al. (Frontiers in Marine Science, 2019)

Identification of clinically relevant features in hypertensive patients using penalized regression: a case study of cardiovascular events - Rafael Garcia-Carretero; Oscar Barquero-Perez; Inmaculada Mora-Jimenez; Cristina Soguero-Ruiz; Rebeca Goya-Esteban; Javier Ramos-Lopez (Medical & Biological Engineering & Computing, 2019)

Influence of mineral waters on in vitro proliferation, antioxidant response and cytokine production in a human lung fibroblasts cell line - Laura María Melgar-Sánchez; Inmaculada García-Ruiz; Virginia Pardo-Marqués; María Teresa Agulló-Ortuño; Inés Martínez-Galán (International Journal of Biometeorology, 2019)

Gut microbial functional maturation and succession during human early life - Tomás Cerdó; Alicia Ruiz; Inmaculada Acuña; Ruy Jáuregui; Nico Jehmlich; Sven‐Bastian Haange; Martin von Bergen; Antonio Suárez; Cristina Campoy (Environmental Microbiology, 2018)
Summary The evolutional trajectory of gut microbial colonization from birth has been shown to prime for health later in life. Here, we combined cultivation‐independent 16S rRNA gene sequencing and metaproteomics to investigate the functional maturation of gut microbiota in faecal samples from full‐term healthy infants collected at 6 and 18 months of age. Phylogenetic analysis of the metaproteomes showed that Bifidobacterium provided the highest number of distinct protein groups. Considerable divergences between taxa abundance and protein phylogeny were observed at all taxonomic ranks. Age had a profound effect on early microbiota where compositional and functional diversity of less dissimilar communities increased with time. Comparisons of the relative abundances of proteins revealed the transition of taxon‐associated saccharolytic and fermentation strategies from milk and mucin‐derived monosaccharide catabolism feeding acetate/propanoate synthesis to complex food‐derived hexoses fuelling butanoate production. Furthermore, co‐occurrence network analysis uncovered two anti‐correlated modules of functional taxa. A low‐connected Bifidobacteriaceae ‐centred guild of facultative anaerobes was succeeded by a rich club of obligate anaerobes densely interconnected around Lachnospiraceae , underpinning their pivotal roles in microbial ecosystem assemblies. Our findings establish a framework to visualize whole microbial community metabolism and ecosystem succession dynamics, proposing opportunities for microbiota‐targeted health‐promoting strategies early in life.

Alteration of neuropathic and visceral pain in female C57BL/6J mice lacking the PPAR-α gene - Jessica Ruiz-Medina; Juan A. Flores; Inmaculada Tasset; Isaac Tunez; Olga Valverde; Emilio Fernandez-Espejo (Psychopharmacology, 2012)

Detection of alpha and betacoronaviruses in multiple Iberian bat species - Ana Falcón; Sonia Vázquez-Morón; Inmaculada Casas; Carolina Aznar; Guillermo Ruiz; Francisco Pozo; Pilar Perez-Breña; Javier Juste; Carlos Ibáñez; Inazio Garin; Joxerra Aihartza; Juan E. Echevarría (Archives of Virology, 2011)

Molecular characterization and evolution of an interspersed repetitive DNA family of oysters - Inmaculada López-Flores; Carmelo Ruiz-Rejón; Ismael Cross; Laureana Rebordinos; Francisca Robles; Rafael Navajas-Pérez; Roberto de la Herrán (Genetica, 2010)

Inhibition of Pichia stipitis fermentation of hydrolysates from olive tree cuttings - Manuel J. Díaz; Encarnación Ruiz; Inmaculada Romero; Cristóbal Cara; Manuel Moya; Eulogio Castro (World Journal of Microbiology and Biotechnology, 2009)